Analisis Kepuasan Kerja Guru Di SMK Negeri 1 Tulung Selapan Kabupaten Ogan Komering Ilir - Kanada, Rabial (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2021)
The teacher is the most important dimension of the education process. Schools must carry out good management of teachers by providing services to realize teacher job satisfaction in schools. In this study using a qualitative approach approach with data sources in this study consisting of primary data and secondary data. Data collection techniques used are interviews, observation and documentation. To analyze the data using the theory of Milles and Humberman. From the results of the study, it can be found that the job satisfaction of teachers at SMK Negeri 1 Tulung Selapan, Ogan Komering Ilir Regency in terms of job satisfaction factors with work, imbalances, supervisory supervisors, coworkers, and appropriate promotions. This means that every point on teacher job satisfaction is not a negative reason for teachers not to carry out optimally. Although at the point of work, there are a small number of teachers who teach not according to their educational qualifications, but personally the individual is not a problem for the teacher. With the artist, the teacher is still comfortable in teaching even though the subjects he teaches are not in accordance with his educational qualifications.